Drying of Kaffir Lime Leaves with Steam Blanching Pre-Treatment using Food Dehydrator - Saumi Nur Rochmani; Asri Widyasanti (Agroindustrial Technology Journal, 2024)
Kaffir lime leaves are a spice plant that is often used by the community as a spice or flavoring for dishes. Kaffir lime leaf spice has a promising business opportunity. However, kaffir lime leaves have a shelf life that is not durable. Post-harvest handling efforts need to be done to extend its shelf life, one way that can be done is by drying. Drying aims to reduce the water content in the material until it reaches a safe moisture content for storage. Drying methods on kaffir lime leaves have been widely practiced. However, the method of drying kaffir lime leaves with pre-treatment blanching using a food dehydrator has not been done much. The purpose of this study was to determine the effect of blanching time on reducing the water content of kaffir lime leaves using a food dehydrator. The materials used in this study were fresh kaffir lime leaves obtained from Bale Tatanen, Faculty of Agriculture, Padjadjaran University. The method used in this research was an experimental method with a completely randomized design (CRD) design with one factor, namely the pretreatment of steam blanching duration (A = 0 minutes; B = 1 minute; and C = 2 minutes). The drying process conditions were carried out at 60â„ƒ for 3 hours with a food dehydrator. The research parameter observed was moisture content. The results showed that 2 minutes steam blanching resulted in the lowest moisture content after drying, from 62.22% (w/b) to 3.27% (w/b).